Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Manajemen Laba: Studi Empiris Pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2023 - Gulo, Kaidir Desman; Fathihani; Randyantini, Vely (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
This article is here to find out the motivation of managers in managing profits, including profitability, leverage and company size. This research is still a hot topic of conversation among researchers, so many studies have been conducted since 2019. This research aims to discuss the influence of profitability, leverage and company size on earnings management in pharmaceutical companies listed on the Indonesian Stock Exchange (IDX) in 2019-2023. This research uses descriptive statistical analysis using secondary data with descriptive statistical tests. Followed by the classical assumption test using the multiple regression model hypothesis testing method. Several conclusions can be drawn that there is profitability which has a positive effect on earnings management, the leverage variable has a negative effect on earnings management, the company size variable has a negative effect on earnings management. It is recommended that further research increase the number of years tested, so that the research results can be more accurate